(untitled) (Comunicação & Inovação, 2023)
This qualitative work sought to establish the characteristics recommended by several theorists for the productions of investigative journalism and environmental journalism, also verifying its similarities. The application of the theory was made by interpretive analysis of three award-winning national investigative reports on environmental issues and a sample of weekly coverage on the environment of the newspaper Folha de S.Paulo. At the end, suggestions are presented to reduce the weaknesses of daily environmental coverage. This coverage could inspire itself on the investigative stories about the theme, in spite of all the differences between deep coverage and daily journalism.